Magnetism and electronic structures of bismuth (stannum) films at the CrI3 (CrBr3) interface. Issue 7 (15th February 2021) - Chen, Li; Jiang, Chuan; Yang, Maoyou; Hu, Tao; Meng, Yan; Lei, Jie; Zhang, Mingjian
Abstract : From first-principles calculations, the magnetism and electronic structures of bilayer bismuth (stannum) films at the monolayer CrI3 (CrBr3 ) interface are studied. Abstract : From first-principles calculations, the magnetism and electronic structures of bilayer bismuth (stannum) films at the monolayer CrI3 (CrBr3 ) interface are studied. The Curie temperature ( T C ) of CrX3 (X = Br, I) can be enhanced by coupling bilayer bismuth (Bi) with van der Waals (vdW) heterostructures. The n-doping of CrX3, induced by interlayer charge-transfer from the Bi film, leads to the enhancement of T C . The quantum spin Hall phases of bilayer bismuth and stannum films are destroyed by the magnetic substrate. Although the interface system of the bilayer stannum (Sn) film on a CrBr3 monolayer shows a band gap (57 meV), the inexistence of edge states with valence and conduction bands connected across the insulating gap is a manifestation of the trivial state without the feature of quantized anomalous Hall effect in the interface. The percentage reduction of the corresponding work function is 22.6%, 12.7%, 25.4% and 16.5% for Bi/CrI3, Sn/CrI3, Bi/CrBr3 and Sn/CrBr3 interface systems, respectively. Our findings demonstrate that the Bi(Sn)–CrI3 (CrBr3 ) interface system with vdW engineering is an efficient way to tune magnetism and electronic structures, which is of importance for future applications in spintronics and nanoelectronics devices.